Dampak Komunikasi Terapeutik terhadap Citra Pelayanan Kesehatan (Studi Kasus di Rumah Sakit Umum Daerah Arifin Achmad Pekanbaru) - Imam Riauan, Muhd. A.R.; Shasrini, Tessa (Universitas Semarang, 2017)
In this paper, we show that the therapeutic communications have to influence the image of health care at Regional Public Hospital of Arifin Achmad Pekanbaru. Beliefs and impressions of the patient have impact to cunstruct the image of health care at the hospital. Communication skills in providing medical services performed in the process of treatment and cure of patients have an effect on increasing the image of the hospital health care. By providing good services communication between doctors or nurses to the patients, health care will improve the image of the hospital. Therapeutic communication are being made to construct a positive image in government hospitals should be done when a doctor or nurse to communicate to the patient to interaction, listening, and to show reception. This paper s result obtain from the quantitative research by using the reggression linear method of statistic.